(untitled) (The Journal of Psychology and Sociology, 2021)
The article examines the professional and psychological cultures of civil servants. The effectiveness of civil servants depends on the implementation of new reforms, the formation of civil society and the nature of interaction between the population and the state. At the same time, it is obvious that the effec- tiveness of the public administration system also depends on the professional and personal qualities and reputation of civil servants. In this regard, currently one of the most pressing problems is the justification of the professional and psychological culture of civil servants of the new formation, directly related to their image. In connection with the information above, this article analyzes the structures and indicators of pro- fessional and psychological culture of civil servants. Character traits and values of civil servants which are an integral part of professional culture are studied. The guarantee of professional culture of civil servants is determined. Substantiation of the components of the professional and psychological culture of civil servants is one of the main objectives of the article. The article states that professional culture is a complex of values and norms of behavior. Therefore, the professional culture of civil servants is one of the indicators of behavior. And the psychological culture is based on the personal qualities of a civil servant. In the practical work, 8 components of the psychological culture of civil servants are identified. There will be studied the characteristics of each component and their significance in relation to civil servants. As shown in practice, the psychological culture of civil servants is formulated by their self-aware- ness, attitude to the environment and themselves, the regulation of their actions, self-esteem, the level of demand on the path of career growth. Key words: Professional and psychological culture, values, components of psychological culture.